27.9k views
1 vote
Simplify the expression i⁸²

1 Answer

1 vote

Answer:

We can use a trick here. Let's look at the first few exponents of i to realize this:

i^0 = 1

i^1 = i

i^2= -1

i^3 = -i

i^4 = 1

i^5 = i

i^6 = -1

i^7 = -i

we can see that the pattern (1, i, -1, -i) repeats. Since 82/2 = 41, and 41 is only divisible by 1, i^41 = i, and i^2 = -1. -1*i = -i, so i^82 = -i.

Explanation:

User Bhavesh Patadiya
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.